Low constant temperature drying can be a satisfactory method to determinethe moisture content of impermeable seed coated species. Issue 4 (20th December 2022) - Jaganathan, Ganesh K; Li, Jiajin; Liu, Baolin
Abstract : The International Seed Testing Association (ISTA) recommends two methods for seed moisture content determination: high constant temperature drying, carried out at 130 °C for 1, 2, 3 or 4 hours, and low constant temperature drying, carried out at 103 °C for 17 hours. However, in species with impermeable seed coats, i.e. physical dormancy (PY), a range of temperatures and duration was used to determine the moisture content. This work found that seeds of Delonix regia (Bojer ex Hook.) Raf., Sesbania grandiflora (L.) Poir. and Adenanthera pavinona L, which all have PY, can reach constant weight between two and five hours when dried at 103 °C for 17 hours. Such high temperatures could either open the water gaps, e.g. the lens in Fabaceae which are present in the seed coat, or crack open the seed coat, as observed during episodes of fire and dry-heat treatments. Therefore, it is suggested that the low constant temperature drying method can be used for species with impermeable seed coats.